Scattering From Controlled Defects in Woodpile Photonic Crystals. Issue 6 (14th January 2021) - Aeby, Stefan; Aubry, Geoffroy J.; Muller, Nicolas; Scheffold, Frank
Abstract: Photonic crystals display partial or full band gaps that become more pronounced with rising refractive index contrast. However, imperfections in the material cause light scattering and extinction of the interfering propagating waves. Positive as well as negative defect volumes may contribute to this kind of optical perturbation. In this study, 3D woodpile photonic crystals are fabricated and characterized with a pseudo‐bandgap for near‐infrared optical wavelengths. By direct laser writing, defects are introduced in the periodic structure at selected positions. It is shown that defect scattering can be modeled by considering the difference between the disordered and the regular structure. The findings pave the way toward better control and understanding of the role of defects in photonic materials that will be crucial for their usability in potential applications. Abstract : Understanding the role of defects in photonic crystals is crucial for their characterization and usability in applications. This article presents an experimental and theoretical investigation of light scattering due to controlled induced imperfections in a periodic 3D woodpile crystal. The total scattering cross‐section is given by the sum of the photonic crystal's intrinsic and the defects scattering contribution.